Reflexiones alrededor del inventario del patrimonio cultural inmaterial ecuatoriano: el registro del santuario de El Quinche - Cabrera Hanna, Santiago (2016)
This article critically evaluates the record of the intangible cultural heritage of Ecuador, conducted within the National Inventory of Cultural Property in the country. Specifically with regard to the definition of intangible cultural heritage established by unesco and its classification in areas and sub areas, the manuscript indicates the problems that the application of these criteria resulted in the inventory, which results in a projected image of the fragmented and dispersed national cultural heritage and, therefore, of culture, whose patrimonial monuments under criteria tends to solidify. This is taken as an example the inventory of the sanctuary of the Virgin of El Quinche.